CD8+ T-Cell Responses in Acute Hepatitis C Virus Infection - Sung, Pil Soo; Racanelli, Vito; Shin, Eui-Cheol (Frontiers in Immunology, 2014)
Hepatitis C virus (HCV) infects approximately 170 million people worldwide and is a major cause of life-threatening liver diseases such as liver cirrhosis and hepatocellular carcinoma. Acute HCV infection often progresses to chronic persistent infection, although some patients recover spontaneously. The divergent outcomes of acute HCV infection are known to be determined by differences in virus-specific T-cell responses among patients. Of the two major T-cell subsets, CD8+ T-cells are known to be the key effector cells that control viral infections via cytolytic activity and cytokine secretion. Herein, we review various aspects of HCV-specific CD8+ T-cell responses in acute HCV infection. In particular, we focus on timing of CD8+ T-cell responses, relationship between CD8+ T-cell responses and outcomes of acute HCV infection, receptor expression on CD8+ T-cells, breadth of CD8+ T-cell responses, and viral mutations.